2020
DOI: 10.1101/2020.01.21.914432
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural differentiation is moderated by age in scene- but not face-selective cortical regions

Abstract: AbstractThe aging brain is characterized by neural dedifferentiation – an apparent decrease in the functional selectivity of category-selective cortical regions. Age-related reductions in neural differentiation have been proposed to play a causal role in cognitive aging. Recent findings suggest, however, that age-related dedifferentiation is not equally evident for all stimulus categories and, additionally, that the relationship between neural differentiation and cognitive perf… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
(69 reference statements)
2
6
1
Order By: Relevance
“…In contrast to previous studies (e.g., Srokova et al, 2020), we did not observe differences in age-related neural dedifferentiation based on stimulus materials.…”
Section: Age-related Neural Dedifferentiation Coexists At Different Rcontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to previous studies (e.g., Srokova et al, 2020), we did not observe differences in age-related neural dedifferentiation based on stimulus materials.…”
Section: Age-related Neural Dedifferentiation Coexists At Different Rcontrasting
confidence: 99%
“…However, when tested by itself, category selectivity also showed to be related to memory performance across participants. The finding that category selectivity was associated with recognition performance while category specificity was not, was also observed by Srokova et al (2020). However, in contrast to that, report a link between recognition memory and both category selectivity and specificity.…”
Section: Age-related Neural Dedifferentiation Coexists At Different Rmentioning
confidence: 76%
See 1 more Smart Citation
“…The available evidence clearly supports the notion of age-related neural dedifferentiation of category information. Focusing on age differences in the representation of broader categories such as faces, houses, or objects within the ventral visual cortex (VVC;Park et al, 2004Park et al, , 2012Payer et al, 2006;Srokova et al, 2020;Voss et al, 2008), previous studies made use of the preferential response of these regions to specific stimulus categories (Epstein and Kanwisher, 1998;Grill-Spector and Malach, 2004;Kanwisher et al, 1997). For example, using conventional univariate analyses, Park et al (2004) demonstrated that, compared to young adults, older adults exhibited less category-selective blood oxygen level dependent (BOLD) responses to stimuli of faces, houses, chairs, and pseudowords, providing the first human evidence for age-related neural dedifferentiation in the VVC (see also Park et al, 2012;Payer et al, 2006, and, accounting for trial-wise BOLD variability: Voss et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Within the visual condition, we chose to present faces and spatial scenes, motivated by work on face-selective and sceneselective brain regions (Kanwisher et al, 1997;Epstein and Kanwisher, 1998;Gazzaley et al, 2005;Collins and Dickerson, 2019). Further, those stimuli seemed to show differences in agerelated reductions in neural dedifferentiation, which makes them interesting for longitudinal studies (Srokova et al, 2020). To select auditory stimuli on a similar level of specificity, we chose voice and environmental stimuli motivated by previous work on voice-selective brain regions (Belin et al, 2000(Belin et al, , 2002Pernet et al, 2015;Agus et al, 2017;Zäske et al, 2017;Aglieri et al, 2018).…”
Section: Introductionmentioning
confidence: 99%